Applying a non-GMO breeding approach with an identified natural variation to reduce food allergen Len c3 in Lens culinaris seeds - Song, Jingpu; Mavraganis, Ioannis; Shen, Wenyun; Yang, Hui; Zou, Jitao (Frontiers in Plant Science, 2024)
Lentils (Lens culinaris) are produced in diverse agroecological regions and are consumed as one of the most important food legumes at world-wide. Lentils possess a nutritional profile from a human health perspective that is not only nutrient-dense but also offers a better balance between protein and carbohydrates. However, lentil causes food allergy which has been a significant concern due to increased consumption in parts of the world. Len c3, a non-specific Lipid Transfer Protein (LTP), was identified as one of the allergens in lentil seeds. In this study, we identified a LTP gene Lcu.2RBY.4g013600 that encodes the lentil allergen Len c3. We then focused on gene screening from a collection of natural accessions to search for natural mutations of the Len c3 allergen-encoding gene. A natural lentil line M11 was identified with mutations at LcLTP3b and low accumulation of vicilin through genomic-assisted approaches. Furthermore, we generated a pool of lentil germplasms with LcLTP3b mutation background through crossing the identified lentil plant M11 with two lentil cultivars, CDC Redmoon and CDC Gold. These generated lentil hybrids can be used as a breeding resource targeting at reducing allergen risk in lentil consumption.